КОМПЬЮТЕР ГРАФИКАСИ ТАЛАБАЛАРНИНГ ФАЗОВИЙ ТАСАВВУРИ РИВОЖЛАНИШИНИНГ ОМИЛИ СИФАТИДА - Дилшодбеков, Ш.Д. (SCIENCE and SOCIETY, 2019)
The author of the article describes the method of using CAD programs software for the development, management and systematization of spatial imagination in students.